1990
DOI: 10.1139/f90-227
|View full text |Cite
|
Sign up to set email alerts
|

Food Chain Structure in Ontario Lakes Determines PCB Levels in Lake Trout (Salvelinus namaycush) and Other Pelagic Fish

Abstract: The trophic structure of pelagic communities in lakes of glaciated regions is highly variable due to restricted dispersal of glacial relict taxa and recent species introductions. Much of the enormous between-lake variability in PCB levels in lake trout flesh (15–10 000 ng/g) from the St. Lawrence system results from differences in the length of pelagic food chains. Ontario Ministry of the Environment data (1978–81) on PCB concentrations in lake trout flesh indicate that PCB concentrations increased with the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
210
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(231 citation statements)
references
References 22 publications
20
210
1
Order By: Relevance
“…In an expanded analysis of the data used by Rasmussen et al (1990), Bentzen et al (1996) found that PCB concentrations in lake trout (Salvelinus namaycush) from different lakes were a function of lipid content, but the intercepts of the regressions differed between lakes. This was attributed to food chain effects and (or) different loading of PCB.…”
Section: Discussionmentioning
confidence: 99%
“…In an expanded analysis of the data used by Rasmussen et al (1990), Bentzen et al (1996) found that PCB concentrations in lake trout (Salvelinus namaycush) from different lakes were a function of lipid content, but the intercepts of the regressions differed between lakes. This was attributed to food chain effects and (or) different loading of PCB.…”
Section: Discussionmentioning
confidence: 99%
“…Organochlorine compounds are persistent toxic pollutants that affect many lakes. Although the more pernicious organochlorine compounds are no longer manufactured in the United States, significant amounts of some compounds still cycle within lakes and enter lakes from the atmosphere (Rasmussen et al 1990, Stow et al 1995. Acid precipitation has several negative impacts on lakes (Schindler et al 1991), including a surprising interaction with stratospheric ozone depletion (D.W. .…”
Section: Figmentioning
confidence: 99%
“…Other, indirect approaches have also led to the conclusion that biomagnification of lipophilic chemicals via the food web is a major contributor to their accumulation in biota at higher trophic levels. Rasmussen et al (1990) concluded that concentrations of PCB in top predators from different lakes increased with increasing length of the food chains, a result attributed to biomagnification. Russell et al (1995) showed that concentrations of some PCBs were greater in white bass (Morone chrysops) than in their prey, emerald shiner (Notropis atherinoides), in Lake Erie, i.e., their biomagnification factors (BMFs) were > 1.…”
Section: Introductionmentioning
confidence: 99%